360* Stewardship - Nowery, Kirk. (Camarillo, Calif. : Spire resources, 2007)
The 360* concept implies all sides, all segments, the full circumference, the entirety. 360* Stewardship is, therefore, the oversight and management of every dimension of life. It is all-encompassing. To be a 360* steward you must wisely, faithfully manage the trust you have been given. That trust for which you are responsible is the sum total of all that you are and have. It is a sacred trust because God himself gave it to you, and his intention is that you steward it in a way that pleases him and yields the greatest return. He wants you to not merely add, but to multiply. That, and much more, is what this book is about.
Carpe diem -- Rapid response -- Influence and impact -- Praying with purpose -- What's in your hand? -- More than money -- Keeping the faith.
Includes bibliographical references.
Keywords: Christian life; Self-realization -- Religious aspects